PENGUKURAN KINERJA PEMERINTAH DAERAH DENGAN MENGGUNAKAN PRINSIP VALUE FOR MONEY PADA DINAS PUPR KABUPATEN ACEH BARAT - Wati Hawala, Linda; Putri, Cut Mega (AKSIOMA : Jurnal Manajemen, 2023)
The problems examined in this study are the Budget Realization Report, reports on changes in Over budget Balance, Balance Sheet, Operational Reports, Changes in Equity Reports, Notes to Financial Statements. In the accountability of this report it was concluded that the PUPR Office of West Aceh District. In its development, the public sector budget system has become a multifunctional policy instrument that is used as a tool to achieve organizational goals. APBD is a regional government financial work plan that will be used as a basis for carrying out development in the region. In preparing, discussing, determining and supervising the implementation of the budget, it is not enough just to look at the size of the budget, but the output must also be produced economically, efficiently and effectively for the development of the region. In this study, the authors wish to analyze the performance of the West Aceh district government by using the principle of value for money which is based on three economic ratios, the ratio of efficiency and ratio of effectiveness. The results of the study show that the performance of the West Aceh District government for the 2020-2021 period as a whole is not good.